Shackelford's surgery of the alimentary tract - Yeo, Charles J (Elsevier, 2013)
Delivers the definitive, clinical oriented guidance you need to achieve optimal outcomes managing the entire spectrum of gastrointestinal disorders. This title uses the endoscopic, robotic, and minimally invasive procedures as well as medical therapies with advice from a who's who of international authorities.